Kinematic analysis of wire stripping for distribution robots based on wire stripping and cutting force control algorithm under cylindrical gear transmission - Liu, Juan; Qiao, Ziqiang (Frontiers in Mechanical Engineering, 2025)
IntroductionThe accurate analysis of Wire Stripping Operation of Power Distribution Robot is crucial for the automation and intelligence of power system maintenance operations. Therefore, a new design and control method for Wire Stripping Operation of Power Distribution Robot has been proposed.MethodsFirstly, a wire stripping device suitable for Cylindrical Gear Transmission was designed. Then, kinematic analysis was conducted based on the Wire Stripping and Cutting Force to ensure the accuracy of the stripping process. Finally, to cope with changes in stiffness environments, an impedance control strategy based on Recursive Least Square method was introduced to improve the stability and adaptability of the control system.ResultsThese results confirmed that the proposed method performs significantly better than traditional methods in force response tracking. When the wire stripping time was 1.9 s, the sinusoidal force responses of the research method, reference force, and general impedance force were −15.3 N, −15.4 N, and −8.2 N, respectively. The sinusoidal force tracking responses were −19.6 N, 6.5 N, 2.6 N to −18.2 N, respectively. The impedance force error curve of the proposed method shows no significant difference compared to the general impedance force error curve (P < 0.05). Meanwhile, the impedance force error curve of the research method was more stable, while the general impedance force error curve fluctuated greatly. Simulation analysis confirmed that the wire stripping surface of the research method was smooth and undamaged, demonstrating the rationality of the wire stripping device design and the superiority of the wire stripping control algorithm. The accuracy, efficiency, and stability scores of the proposed method are superior to the other three classical control methods.DiscussionThis study is crucial for improving the automation level and operational accuracy of wire stripping operations in power distribution robots.